Pengaruh Likuiditas Terhadap Kebijakan Dividen Dengan Profitabilitas Sebagai Variabel Intervening (Studi Empiris Perusahaan LQ 45 yang Terdaftar di BEI Periode 2011-2015) - Silviana Sapitri; Emma Suryani (Sains: Jurnal Manajemen dan Bisnis, 2018)
The aimed of this study is investigate whether the liquidity affect the dividend policy, using profitabilty is able to intervening variable. In this study, the dividend policy is measured by dividend payout ratio, liquidity measured by current ratio, and profitability measured by return on equity.In addition, the sample obtain from LQ 45 company, which are listed on the Indonesian Stock Exchange (IDX) from 2011-2015 and gathered 12 firms-years observation as sample with purposive sampling method. The analytical method are using outlier test, classic assumption test, partial test (t test) and path analysis. From hypothesis result by using t test and path analysis shos that: 1) liquidity don’t have a significant effect on profitability, 2) liquidity and profitability don’t have a significant effect on dividend policy; profitability can not be intervening the relationship of liquidity and dividend policy value.